Fruits, frugivores, and the evolution of phytochemical diversity. Issue 2 (14th June 2021) - Whitehead, Susan R.; Schneider, Gerald F.; Dybzinski, Ray; Nelson, Annika S.; Gelambi, Mariana; Jos, Elsa; Beckman, Noelle G.
Abstract : Plants produce an enormous diversity of secondary metabolites, but the evolutionary mechanisms that maintain this diversity are still unclear. The interaction diversity hypothesis suggests that complex chemical phenotypes are maintained because different metabolites benefit plants in different pairwise interactions with a diversity of other organisms. In this synthesis, we extend the interaction diversity hypothesis to consider that fruits, as potential hotspots of interactions with both antagonists and mutualists, are likely important incubators of phytochemical diversity. We provide a case study focused on the Neotropical shrub Piper reticulatum that demonstrates: 1) secondary metabolites in fruits have complex and cascading effects for shaping the outcome of both mutualistic and antagonistic fruit–frugivore interactions, and; 2) fruits can harbor substantially higher levels of phytochemical diversity than leaves, even though leaves have been the primary focus of plant chemical ecology research for decades. We then suggest a number of research priorities for integrating chemical ecology with fruit–frugivore interaction research and make specific, testable predictions for patterns that should emerge if fruit interaction diversity has helped shape phytochemical diversity. Testing these predictions in a range of systems will provide new insight into the mechanisms driving frugivory and seed dispersal and shape an improved, whole‐plant perspective on plant chemical trait evolution.